Meta-Analysis Comparing Renal Outcomes after Transcatheter versus Surgical Aortic Valve Replacement - Kuldeep Shah; Zakeih Chaker; Tatiana Busu; Rishita Shah; Mohammed Osman; Fahad Alqahtani; Mohamad Alkhouli (Journal of Interventional Cardiology)
Background. Acute kidney injury (AKI) is a common complication of aortic valve replacement. However, comparative on the incidence of (AKI) following transcatheter (TAVR) versus surgical valve replacement (SAVR) is sparse. Methods. We performed a meta-analysis of the randomized controlled trials (RCT) and propensity-matched observational studies comparing (A) incidence of AKI and (B) incidence of dialysis-requiring AKI at 30 days after TAVR and SAVR. Results. Twenty-six studies (20 propensity-matched studies; 6 RCTs) including 19,954 patients were analyzed. The incidence of AKI was lower after TAVR than after SAVR (7.1% vs. 12.1%, OR 0.52; 95%CI, 0.39-0.68; p<0.001, I2=57%), but the incidence of dialysis-requiring AKI was similar (2.8% vs. 4.1%, OR 0.78; 95%CI, 0.49-1.25; p=0.31, I2=70%). Similar results were observed in a sensitivity analysis including RCTs only for both AKI ([5 RCTs; 5,418 patients], 2.0% vs. 5.0%, OR 0.39; 95%CI, 0.28-0.53; p<0.001, I2=0%), and dialysis-requiring AKI ([2 RCTs; 769 patients]; 2.9% vs. 2.6%, OR 1.1; 95%CI, 0.47-2.58; p=0.83, I2=0%). However, in studies including low-intermediate risk patients only, TAVR was associated with lower incidence of AKI ([10 studies; 6,510 patients], 7.6% vs. 12.4%, OR 0.55, 95%CI 0.39-0.77, p<0.001, I2=57%), and dialysis-requiring AKI, ([10 studies; 12,034 patients], 2.0% vs. 3.6%, OR 0.57, 95%CI 0.38-0.85, p=0.005, I2=23%). Conclusions. TAVR is associated with better renal outcomes at 30 days in comparison with SAVR, especially in patients at low-intermediate surgical risk. Further studies are needed to assess the impact of AKI on long-term outcomes of patients undergoing TAVR and SAVR.